2020
DOI: 10.3390/healthcare8020155
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of COVID-19-Related Deaths among General Practitioners in Italy

Abstract: To date, data on COVID-19-related death cases among physicians from different medical specialties are incomplete and scattered. In Italy, available data highlight that general practitioners (GPs) are, apparently, the most heavily affected group. Indeed, they currently represent 44.1% of the total COVID-19 related death cases occurred among physicians, whereas they constitute about 15% of the total number of doctors. This high proportion is most likely the consequence of a work-related contagion happening espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 11 publications
2
25
1
1
Order By: Relevance
“…In fact, most Italian GPs still work single-handedly in solo practices that are somewhat isolated from the rest of the NHS ( 26 ). Indeed, a recent study showed how Italian GPs represent 44.1% of the total COVID-19-related deaths among doctors, and organizational issues (i.e., working alone), along with the lack of PPE, were proposed as explanations for the high burden suffered by GPs ( 27 ). Moreover, in many regions of Italy such as Lombardy, regional policies fostered a strong hospital-centric organization while primary care has been underfinanced for many years ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, most Italian GPs still work single-handedly in solo practices that are somewhat isolated from the rest of the NHS ( 26 ). Indeed, a recent study showed how Italian GPs represent 44.1% of the total COVID-19-related deaths among doctors, and organizational issues (i.e., working alone), along with the lack of PPE, were proposed as explanations for the high burden suffered by GPs ( 27 ). Moreover, in many regions of Italy such as Lombardy, regional policies fostered a strong hospital-centric organization while primary care has been underfinanced for many years ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…"The total lack of preparation to face the biggest emergency in the area since the Second World War with an excessively hospitalcentered vision caused the wards to become saturated within a week." (27) "Much more attention is needed on primary care, which in this emergency has been abandoned to give resources to the hospital." (73)…”
Section: Organization Of the Primary Care Servicesmentioning
confidence: 99%
“…It is important to finalize strategies and procedures to prevent SARS-CoV-2 infection among GPs, for example, specific guidelines for GPs to safely guarantee care for patients during the spread of COVID-19. Another input could be the introduction of telemedicine procedures to reduce direct contact with patients [10,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Modenese and Gobba reported that 44% of the COVID-19 related deaths among Italian physicians were GPs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Italian health system was heavily challenged by this unexpected pandemic that represented the first health priority for the following months. As of May 26, 2020, 126 physicians among general practitioners and physicians who were in the front line died of COVID-19 infection 1 . As a result of the pandemic, the dermatologic community consistently diminished most activities, reducing by 80-90% the outpatient consultation both in public hospitals and in private offices 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%